2002
DOI: 10.1016/s0378-1127(01)00623-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in salt tolerance of selected boreal woody seedlings

Abstract: In order to select woody plant candidates suitable for revegetation of saline-alkaline soils, we tested selected woody plant species and seed lots: Pinus contorta (lodgepole pine), Pinus banksiana (jack pine), Picea glauca (white spruce), Populus tremuloides (trembling aspen), and Alnus rubra, syn. Alnus oregona (red alder). Pre-germinated seedlings were grown for 4 weeks in a greenhouse in a semi-hydroponic system containing 1/2 strength Hoagland solution with additional sodium concentrations (0, 25, 50, 75 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Characteristics like long leaf lifespan (Greenway et al 1992;Munson et al 1995;Claveau et al 2002), high leaf mass per leaf area (Claveau et al 2005), and high plasticity in crown morphology (Messier et al 1999) that help white spruce survive in low resource availability conditions in the forest understory could also help it survive in unfavorable soils. Khasa et al (2002) also found that white spruce was slow growing, yet had high survivorship in a comparative salinity experiment.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Characteristics like long leaf lifespan (Greenway et al 1992;Munson et al 1995;Claveau et al 2002), high leaf mass per leaf area (Claveau et al 2005), and high plasticity in crown morphology (Messier et al 1999) that help white spruce survive in low resource availability conditions in the forest understory could also help it survive in unfavorable soils. Khasa et al (2002) also found that white spruce was slow growing, yet had high survivorship in a comparative salinity experiment.…”
Section: Discussionmentioning
confidence: 86%
“…In one study, every aspen seedling growing in a 2 dS m (1 hydroponic NaCl salinity treatment died within 1 mo (Khasa et al 2002), and in other studies white spruce seedlings had reduced growth at electrical conductivities as low as 0.5 dS m…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Alders have been found to increase soil total nitrogen and carbon (Martin et al, 2003). In addition to thriving in low nitrogen conditions, alders have been reported to support growth in salt affected environments (Graves and Gallagher, 2003;Mertens et al, 2004) and in composite tailings (Khasa et al, 2002). Alder growth was monitored in oil-shale mining detritus and found to be comparable to that recorded on two reference fertile sites (Vares et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Recent laboratory and greenhouse research has focused on quantifying the effects of salinity on boreal species (e.g., Renault et al 1999;Khasa et al 2002;Nguyen et al 2006). We chose a fieldbased approach, using the rare naturally-saline forested sites that exist adjacent to non-forested saline wetlands in the boreal mixedwood region.…”
mentioning
confidence: 99%